Artificial hydrogenases: Assembly of an H-cluster analogue within a functionalised poly(pyrrole) matrix - Ibrahim, S.; Woi, P.M.; Alias, Y.; Pickett, C.J. (Royal Society of Chemistry, 2010)
We show that a redox active {Fe(4)S(4)}(2+)-cubane assembly covalently bound within a cysteinyl-alkylammonium functionalised polypyrrole can be modified with a diiron dithiolate carbonyl unit to give an artificial hydrogenase H-cluster framework confined within the polymer matrix.